The Implementation of Cooperative Learning Model For Critical Thinking Skills in the History Subject at SMA Pekanbaru - Isjoni (Prodi Administrasi Pendidikan Program Pascasarjana Universitas Riau, 2017)
In the approach to learning, teachers must be able to create an active, creative, effective, and fun learning. One of the learning approaches that can be used to create this active, creative, effective and fun learning in a group is cooperative learning. Jigsaw was particularly selected from various types of cooperative learning. It was because it is used by researchers in science education, and less popular in social science education. Jigsaw arouse students' attitudes to learning, including in the History subject. Jigsaw that is one ofthe types of cooperative learning models that encourages students to be active and help each others in mastering the subject matter to achieve maximum performance. The aim of the study was to see the different models of cooperative learning on students' critical thinking skills in the History subject. The method used was by using the test statistics with analysis using Excel for Windows. To determine whether there is any differences, tests of paired data (Student's t-test) were conducted. If there are no significant differences between the dependent variable for the pre-test, it will be used followed by ANOVA in the post test. The results showed that there is a difference between the type of cooperative learning model jigsaw with traditional learning in the study on the critical thinking skills of students in the History subject.